Starting strong : a mentoring fable - Zachary, Lois J. (Jossey-Bass, A Wiley Brand, 2014)
"Story is a very powerful way to exemplify concepts and show the dynamics and issues involved in relationships. In this mentoring fable, Zachary and Fischler use the story of an incipient mentoring relationship and its possibilities, problems, and pitfalls to bring their suggestions for best practices to life. The first 90 days of a mentoring relationship are relatively fragile; as both mentor and mentee proceed uncertainly, they may not know how to create the ingredients that are crucial to its success: building trust, finding their comfort zones (and having the courage to leave them), setting up productive regular meetings and conversations, dealing with power dynamics, setting goals, and keeping momentum going. While the fable offers tools and skills that can be applied to any mentoring relationship, Zachary and Fischler also provide a conversation playbook for new mentoring relationships, with guidance for establishing a mentoring relationship and keeping it strong"--